Immunization of Mice with Live-Attenuated Late Liver Stage-Arresting Plasmodium yoelii Parasites Generates Protective Antibody Responses to Preerythrocytic Stages of Malaria - Keitany, Gladys J. (Infect Immun, 2014)
Understanding protective immunity to malaria is essential for the design of an effective vaccine to prevent the large number of infections and deaths caused by this parasitic disease. To date, whole-parasite immunization with attenuated parasites is the most effective method to confer sterile protection against malaria infection in clinical trials. Mouse model studies have highlighted the essential role that CD8(+) T cells play in protection against preerythrocytic stages of malaria; however, there is mounting evidence that antibodies are also important in these stages. Here, we show that experimental immunization of mice with Plasmodium yoelii fabb/f(−) (Pyfabb/f(−)), a genetically attenuated rodent malaria parasite that arrests late in the liver stage, induced functional antibodies that inhibited hepatocyte invasion in vitro and reduced liver-stage burden in vivo. These antibodies were sufficient to induce sterile protection from challenge by P. yoelii sporozoites in the absence of T cells in 50% of mice when sporozoites were administered by mosquito bite but not when they were administered by intravenous injection. Moreover, among mice challenged by mosquito bite, a higher proportion of BALB/c mice than C57BL/6 mice developed sterile protection (62.5% and 37.5%, respectively). Analysis of the antibody isotypes induced by immunization with Pyfabb/f(−) showed that, overall, BALB/c mice developed an IgG1-biased response, whereas C57BL/6 mice developed an IgG2b/c-biased response. Our data demonstrate for the first time that antibodies induced by experimental immunization of mice with a genetically attenuated rodent parasite play a protective role during the preerythrocytic stages of malaria. Furthermore, they highlight the importance of considering both the route of challenge and the genetic background of the mouse strains used when interpreting vaccine efficacy studies in animal models of malaria infection.